2018
DOI: 10.1002/jcp.26950
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Downregulated microRNA‐488 enhances odontoblast differentiation of human dental pulp stem cells via activation of the p38 MAPK signaling pathway

Abstract: Human dental pulp stem cells (hDPSCs) are primarily derived from the pulp tissues of permanent third molar teeth. They were widely used in human bone tissue engineering. It was previously indicated that microRNA (miR) expressions are closely associated with hDPSCs development. However, the specific effect of miR-488 on hDPSCs still remains unclear. In this study, we aimed to investigate effects of miR-488 on the differentiation of hDPSCs into odontoblast cells through the p38 mitogen-activated protein kinases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…The role of miR-488 in inflammation has been reported (Vergadi, Vaporidi, & Tsatsanis, 2018;Yu et al, 2019;Zhou et al, 2017). However, its biological function is currently unclear in endometritis.…”
Section: Discussionmentioning
confidence: 99%
“…The role of miR-488 in inflammation has been reported (Vergadi, Vaporidi, & Tsatsanis, 2018;Yu et al, 2019;Zhou et al, 2017). However, its biological function is currently unclear in endometritis.…”
Section: Discussionmentioning
confidence: 99%
“…In the research on ncRNAs and their roles in the odontogenic differentiation of hDPSCs, the most studied are miRNAs. miR-223-3p and miR-21 have been shown to promote odontogenic differentiation, while miR-143-5p, miR-140-5p, and miR-488 inhibit this process [41][42][43][44][45][46]. In 2016, Chen et al found that lncRNA differentiation antagonizing non-protein coding RNA (DANCR) inhibited the odontogenic differentiation of human dental pulp cells by inactivating the Wnt/β-catenin signaling pathway [16].…”
Section: Discussionmentioning
confidence: 99%
“…Heatmap representing the proportion of publications by year that utilized specific translational research methodologies from construct characterization to human trial to investigate craniofacial tissue engineering 49‐72,74‐77,79,81‐84,145‐197 …”
Section: Discussionmentioning
confidence: 99%